2003
DOI: 10.1042/cs20020312
|View full text |Cite
|
Sign up to set email alerts
|

Chronic α-tocopherol supplementation in rats does not ameliorate either chronic or acute alcohol-induced changes in muscle protein metabolism

Abstract: Chronic alcohol muscle disease is characterized by reduced skeletal muscle mass precipitated by acute reduction in protein synthesis. The pathogenic mechanisms remain obscure, but several lines of evidence suggest that increased oxidative stress occurs in muscle in response to alcohol and this may be associated with impaired alpha-tocopherol status. Potentially, this implies a therapeutic role for alpha-tocopherol, especially as we have shown that supplemental alpha-tocopherol may increase the rate of protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The negative effects of chronic alcohol ingestion on skeletal muscle redox state have been well‐documented (Adachi et al., 2000; Fernández‐Solà et al., 2002; Koo‐Ng et al., 2000; Otis et al., 2007; Preedy et al., 2001). However, most alcohol studies that attempted to attenuate alcohol‐induced oxidant stress with antioxidant or antioxidant cofactor supplementation have reported limited successes (Durán Castellón et al., 2005;Koll et al., 2003; Reilly et al., 2000). In contrast, we have previously shown that procysteine restored muscle GSH levels in rats fed alcohol for 6 weeks while reducing oxidant stress and mRNA expression of 2 catabolic factors, atrogin‐1 and TGFβ 1 (Otis et al., 2007)—each occurring despite the absence of clinical alcoholic myopathy (e.g., atrophy).…”
Section: Discussionmentioning
confidence: 99%
“…The negative effects of chronic alcohol ingestion on skeletal muscle redox state have been well‐documented (Adachi et al., 2000; Fernández‐Solà et al., 2002; Koo‐Ng et al., 2000; Otis et al., 2007; Preedy et al., 2001). However, most alcohol studies that attempted to attenuate alcohol‐induced oxidant stress with antioxidant or antioxidant cofactor supplementation have reported limited successes (Durán Castellón et al., 2005;Koll et al., 2003; Reilly et al., 2000). In contrast, we have previously shown that procysteine restored muscle GSH levels in rats fed alcohol for 6 weeks while reducing oxidant stress and mRNA expression of 2 catabolic factors, atrogin‐1 and TGFβ 1 (Otis et al., 2007)—each occurring despite the absence of clinical alcoholic myopathy (e.g., atrophy).…”
Section: Discussionmentioning
confidence: 99%
“…For example, providing alcoholics dietary supplements of zinc, an essential cofactor for superoxide dismutase and glutathione peroxidase, did not alleviate symptoms of alcoholic myopathy (Ferna´ndez-Sola`et al, 1998). Further, a-tocopherol supplementation had little effect on the rates of protein synthesis or the total protein content in skeletal muscle (Koll et al, 2003). Moreover, precursors of the nonvitamin antioxidant glutathione have been used to rectify alcohol-induced derangements to lung and skeletal muscle tissue (Otis and Guidot, 2009;Otis et al, 2007;Velasquez et al, 2002).…”
Section: Glutathione Restoration As An Intervention For Alcoholic Myomentioning
confidence: 99%
“…(2004). Intervention studies with chronic alpha‐tocopherol and zinc supplementation in rats do not ameliorate either chronic or acute alcohol‐induced muscle changes (Durán‐Castellón et al., 2005; Koll et al., 2003; Reilly et al., 2000b) and in some instances may be damaging in the dosage regimens used (see Koll et al., 2003). The exception appears to be studies with uncoupling protein 3 (UCP3) mRNA, which is reduced in alcohol exposure but ameliorated with alpha‐tocopherol supplementation (Baffy et al., 2006a,b).…”
Section: Historical Timeline Events In Alcoholic Myopathiesmentioning
confidence: 99%
“…Oxidative alteration of structural proteins may also alter protein degradation (Basoah et al., 2005). Decreased protein synthesis is a well‐described feature in alcoholic myopathy (Hunter et al., 2003; Lang et al., 2001; Preedy et al., 2001); however, available data do not support an unequivocal role of oxidative stress in its pathogenesis (Koll et al., 2003).…”
Section: Trace Elements and Oxidative Stress In Alcoholic Myopathymentioning
confidence: 99%